Some LRS Bianchi type-II string-dust cosmological models in general relativity - Amirhashchi, Hassan; Zainuddin, Hishamuddin (Electronic Journal of Theoretical Physics, 2010)
Some LRS Bianchi type-II string-dust cosmological models are investigated in which the expansion (θ) is assumed to be proportional to the shear (σ). To obtain exact solutions, the Einstein’s field equations have been solved for two cases (i) Reddy string and (ii) Nambu string. The physical and geometrical behaviour of these models are discussed.